HUBUNGAN INDEKS MASSA TUBUH DENGAN FRAILTY PADA LANSIA DI PPRSLU BUDI SEJAHTERA BANJARBARU - Ansharullah, M Rifky; Cahyawati, Wiwit Agung Sri Nur; Yasmina, Alfi; Noor, Zairin; Wahyuni, Wahyuni (Homeostasis, 2024)
Abstract: Frailty is a sign of physiological and functional vulnerability in the elderly. One of the risk factors for frailty is BMI. This study aimed to determine the relationship between BMI and frailty in the elderly, using cross-sectional method. The research subjects were elderliesliving in PPRSLU Budi Sejahtera Banjarbaru, using total sampling method according to the inclusion and exclusion criteria. The independent variable was BMI and the dependent variable was frailty. Frailty was measured by physical frailty phenotype. The relationship between BMI and frailty was analyzed using the logistic regression test. A total of 40 elderlies were included; most were women with an average age of 69.8 ± 8.6 years and an average BMI of 23.4 ± 4.6 kg/m2. There were no robust/fit elderlies. Elderlies with underweight and normal BMI tended to be frail, while elderlies with overweight and obese BMI tended to be pre-frail. Increasing BMI was associated with a lower incidence of frailty compared with the pre-frail incidence, but this relationship was not significant (OR 0.53, 95%CI = 0.24-1.17). The conclusion of this research is that there is no significant relationship between BMI and frailty in the elderlies living in PPRSLU Budi Sejahtera Banjarbaru. Keywords: frailty, body mass index, elderly, physical frailty phenotype. Abstrak: Frailty merupakan tanda kerentanan fisiologis dan fungsional pada lansia. Salah satu faktor risiko frailty adalah IMT. Penelitian ini bertujuan mengetahui hubungan IMT dengan frailty pada lansia, dengan metode cross-sectional. Subjek penelitian yaitu lansia di PPRSLU Budi Sejahtera Banjarbaru, menggunakan metode total sampling sesuai kriteria inklusi dan eksklusi. Variabel bebas adalah IMT dan variabel terikatnya frailty. Frailty diukur dengan physical frailty phenotype. Hubungan IMT dan frailty dianalisis dengan uji logistic regression. Sebanyak 40 lansia diinklusi; sebagian besar perempuan dengan rerata usia 69,8±8,6 tahun dan rerata IMT 23,4±4,6 kg/m2. Tidak didapatkan lansia yang robust/fit. Lansia dengan IMT underweight dan normal cenderung frail, sedangkan lansia IMT overweight dan obesitas cenderung pre-frail. Peningkatan IMT berhubungan dengan kejadian frailty yang lebih rendah dibanding kejadian pre-frail, namun hubungan ini tidak bermakna (OR 0,53, 95%CI = 0,24-1,17). Simpulan penelitian ini adalah tidak terdapat hubungan yang signifikan antara IMT dan frailty pada lansia di PPRSLU Budi Sejahtera Banjarbaru. Kata-kata kunci: frailty, indeks massa tubuh, lansia, physical frailty phenotype